(untitled) (e-Journal of Linguistics, 2026)
This study aims to describe the function of illocutionary acts conveyed by speakers to their interlocutors in communication, reviewed from a pragmatic perspective, particularly illocutionary acts. This study uses a qualitative approach because the research data consists of conversations between characters in the form of dialogues. The source of data in this study is the film Tenggelamnya Kapal Van Der Wijck (The Sinking of the Van Der Wijck) directed by Sunil Soraya. The data collection technique uses the observation and note-taking methods. The data analysis technique uses the matching method. The findings on speech functions were analyzed using Leech’s theory. According to Leech’s theory, illocutionary speech acts are divided into four types, which were used as data, totaling 38 data points. These 38 data points were divided into 5 competitive data points, 13 convivial data points, 14 collaborative data points, and 6 conflictive data points. In addition, the film Tenggelamnya Kapal Van Der Wijck teaches us that true love knows no boundaries of religion, race, and culture. However, in pursuing love, one must uphold good values in life and uphold the dignity of oneself and one’s family.